Parzival : With Titurel and the Love Lyrics. - Von Eschenbach, Wolfram (Boydell & Brewer, 2004)
Vast in its scope, incomparably dense in its imagery, Wolfram von Eschenbach's Parzival ranks alongside Dante's Divine Comedy as one of the foremost narrative works to emerge from medieval Europe. This book is a new translation of Parzival, together with the fragments of the Titurel, an elegiac offshoot of Parzival, and the nine love-songs attributed to Wolfram.